EFFECT OF OXALIC ACID, NA+, NH4 +, AND FE3+ ON AVAILABILITY OF SOIL K, PLANT N, P, AND K UPTAKE, AND MAIZE YIELD IN SMECTITIC SOILS - NURSYAMSI, DEDI; IDRIS, K.; SABIHAM, SUPIYANDI; RACHIM, D.A; SOFYAN, AGUS (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2008)
Smectitic soils have high prospect to be developed for agricultural land under a proper soil and plant management. The soils are commonly high in total K content. It?s availability for plant growth, however, is relatively low due to fixation by smectite in interlayer space. Researches aimed to study the effect of oxalic acid, Na+, NH4+, and Fe3+ on availability of soilK, plant N, P, and K uptake, as well as maize yield in smectitic soils have been conducted in Laboratory of Research and Soil Test and Green House of Indonesian Soil Research Institute, Bogor. Four different types of bulk soil samples taken from Bogor (Typic Hapludalfs), Cilacap (Chromic Endoaquerts), Ngawi (Typic Endoaquerts), and Blora (Typic Haplustalfs) were used for experiments. Incubation and pot experiments were set up using Factorial Randomized Completely Block Design with three replication and pot experiment used maize of Pioneer 21 variety as plant indicator. The first factor was oxalic acid rates: 0; 1,000; 2,000; and 4,000 ppm, while the second one was application of cations: without cation, Na+, NH4+, and Fe3+ from NaCl, NH4Cl, and FeCl3 respectively with 50% of maximum adsorption rate. The Fe3+ with 50% of maximum adsorption rate caused plant death, thus the experiment was repeated in the nextseason with Fe3+ rates: 0, 125, 250, 375, and 500 ppm. The results showed that oxalic acid, Na+, NH4+, and Fe3+ significantly increased the availability of soil K in both Alfisols and Vertisols where the effect was higher in Vertisols than Alfisols. The effectiveness of the treatments to release K from non available to available K form in the soils was in order of Fe3+ > NH4+ > Na+ > oxalic acid. Oxalic acid significantly increasedplant N, P, and K uptake in Vertisols, while 125 ppm of Fe3+ significantly increased plant K uptake in Alfisols as well as N, P, and K uptake in Vertisols. Oxalic acid significantly increased 4- week-after-planting biomass dry yield in Typic Hapludalfs and Typic Endoaquerts, while 125 ppm of Fe3+ significantly increased the yield in Chromic Endoaquerts and Typic Endoaquerts.